A Review of Switching Strategies for Patients with Schizophrenia Comorbid with Metabolic Syndrome or Metabolic Abnormalities - Liao X; Ye H; Si T (Neuropsychiatric Disease and Treatment, 2021)
Xuemei Liao,1,* Hui Ye,2,* Tianmei Si1 1Peking University Sixth Hospital, Peking University Institute of Mental Health, NHC Key Laboratory of Mental Health (Peking University), National Clinical Research Center for Mental Disorders (Peking University Sixth Hospital), Beijing, 100191, People’s Republic of China; 2Medical Department, Sanofi, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Tianmei SiPeking University Sixth Hospital, Peking University Institute of Mental Health, NHC Key Laboratory of Mental Health (Peking University), National Clinical Research Center for Mental Disorders (Peking University Sixth Hospital), Huayuanbeilu 51#, Haidian District, Beijing, 100191, People’s Republic of ChinaTel +86 13910987793Email si.tian-mei@163.comAbstract: Metabolic syndrome (MetS) in patients with schizophrenia occurs 2– 3 times more frequently than in the general population. Antipsychotic medication is a primary risk factor for patients with MetS. In particular, the widely used second-generation antipsychotics can affect glucose and lipid metabolism and can induce insulin resistance and other metabolic abnormalities through various receptors. Notably, the metabolic risks of various antipsychotics may differ because of their different pharmacological affinity to MetS-related receptors. Several previous studies have shown that switching from high to low metabolic risk antipsychotics may improve patients’ metabolic parameters. The current review aims to discuss the strategies for switching antipsychotic medications and the impact on metabolic abnormalities in patients with schizophrenia.Keywords: antipsychotics, switch, metabolic syndrome